Simultaneous identifying the infarct core, collaterals, and penumbra after acute ischemic stroke with a low-immunogenic MRI nanoprobe - Peisen Zhang; Wenyue Li; Chuang Liu; Lichong Zhu; Junwei Cheng; Runxin Pang; Yue Lan; Meng Qin; Yi Hou (Materials & Design, 2023)
Ischemic stroke is one of the leading causes of disability and mortality. The collaterals provide an alternative pathway to preserve the ischemic brain tissue, and determine the penumbra range, where the neurons are salvageable. Therefore, accurately monitoring the collaterals and identifying the penumbra are crucial. Herein, a low-immunogenic nanoprobe-based MRI strategy is developed to simultaneously identify the infarct core, collaterals distribution, and ischemic penumbra distributions. The low-immunogenic nanoprobe was constructed by covalently attaching self-peptide on the surface of biocompatible Fe3O4 nanoparticles as a stealth coating. Both in vitro and in vivo experiments clearly revealed that the nanoprobes can effectively avoid capture by macrophages, and exhibited prolonged blood half-life to continuously enhance the contrast of blood vessels in a longer time window in susceptibility-weighted imaging (SWI), which enabled the delineation of the collaterals and ischemic penumbra. More importantly, combined with the diffusion-weighted imaging (DWI), the infarct core, collateral vessels, and the ischemic penumbra range can be identified simultaneously. In this context, the stroke progress including infarct core growth, collateral vessel formation, and penumbra distribution, can be better understood. This nanoprobe-based strategy thus offers a practical route for precise diagnosis of ischemic stroke, which remains a challenge for conventional MRI strategies.